2019
DOI: 10.32553/ijmbs.v3i6.287
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Assessment and Perceived Stress Amongst Medical Postgraduate Residents

Abstract: Background: Medical graduates who enter into residency programmes form the backbone of the healthcare delivery system of the country. They are often expected to work for long hours which leads to sleep deprivation and increase in the perceived stress levels. Chronic sleep deprivation leads to destruction of sleep architecture. It may also compromise patient care. We examine the relationship between these two variables through this study. Material and methods: 50 resident doctors from different specialtie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The mean value of ESS was 9.07±3.85.Our study was comparable with studies conducted by Siddalingaiah HS et al and by Sharma A et al, where the prevalence of daytime sleepiness among post graduate students was 47.4% and 33.3% respectively .8,9 Average sleep time: According to the Mayo clinic, the average sleep time of adults should be between 7-9 hrs and total time less than 7 hours is considered as insufficient sleep or sleep deprivation. 10 The present study has indicated that 182 (66%) post graduate students had<7hrs of sleep which is comparable with the study conducted by Garg S 10 In the present study majority (62%) of sleep deprived post graduate students were doing night duties whereas opposite trend was observed among non-sleep deprived, where 67% were not doing night duties. This difference was found to be statistically significant..…”
Section: Discussionsupporting
confidence: 88%
“…The mean value of ESS was 9.07±3.85.Our study was comparable with studies conducted by Siddalingaiah HS et al and by Sharma A et al, where the prevalence of daytime sleepiness among post graduate students was 47.4% and 33.3% respectively .8,9 Average sleep time: According to the Mayo clinic, the average sleep time of adults should be between 7-9 hrs and total time less than 7 hours is considered as insufficient sleep or sleep deprivation. 10 The present study has indicated that 182 (66%) post graduate students had<7hrs of sleep which is comparable with the study conducted by Garg S 10 In the present study majority (62%) of sleep deprived post graduate students were doing night duties whereas opposite trend was observed among non-sleep deprived, where 67% were not doing night duties. This difference was found to be statistically significant..…”
Section: Discussionsupporting
confidence: 88%
“…Stress decreases muscle power due to its catabolic effect on muscle proteins. A strong relationship exists between the decreased quality of sleep, more daytime sleep, and high perceived stress (Ajgaonkar et al, 2019). Since the stress system is essential for coping with demanding environments, it is crucial to evaluate how disrupted sleep affects this system and how both perceived stress and sleep loss affect muscle function.…”
Section: Introductionmentioning
confidence: 99%
“…Literature regarding the assessment of sleep quality among medical residents is limited (23)(24)(25)(26). Available studies show that 45% to 90% of medical residents report poor sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Available studies show that 45% to 90% of medical residents report poor sleep quality. Poor sleep quality has been associated with fatigue, memory lapses, perceived stress, heartburn, irritable bowel syndrome and depression among medical residents (23)(24)(25). Considering the inclusive nature of "sleep quality", it is possible that sleep quality might influence the CIMT among medical residents, as has been observed among middle-aged women (27).…”
Section: Introductionmentioning
confidence: 99%